2007
DOI: 10.1354/vp.44-6-875
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Multiple Myeloma 1/Interferon Regulatory Factor 4 (MUM1/IRF-4) in Canine Plasmacytoma: Comparison with CD79a and CD20

Abstract: Abstract. Multiple myeloma oncogene 1/interferon regulatory factor 4 (MUM1/IRF4) is involved in lymphoid cell differentiation, particularly in the production of plasma cells. We examined the immunoreactivity of mouse monoclonal antibody Mum-1p to MUM1/IRF4 and compared it with expression of CD79a and CD20 in 109 plasmacytomas in 107 dogs. Tissues had been fixed in formalin and embedded in paraffin. One hundred one of 109 (93.5%) tumors were positive for MUM1/IRF4. The staining was nuclear with weak cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
140
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 52 publications
3
140
2
1
Order By: Relevance
“…Other authors observed positive staining for CD79a in 59 (56.2%) of 105 cases of PCT (Ramos-Vara et al 2007). In the present study, the tumours deϐined as PCTs were positive for CD79a in 66.66% (6/9) of the cases, and the labelling was predominantly cytoplasmic diffuse.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Other authors observed positive staining for CD79a in 59 (56.2%) of 105 cases of PCT (Ramos-Vara et al 2007). In the present study, the tumours deϐined as PCTs were positive for CD79a in 66.66% (6/9) of the cases, and the labelling was predominantly cytoplasmic diffuse.…”
Section: Discussionmentioning
confidence: 88%
“…Immunohistochemical markers such as CD79a (Schrenzel et al 1998) and immunoglobulins (Platz et al 1999) have been used as ancillaries in the diagnosis of this neoplasm. Variable immunohistochemical expression of the CD79a antigen has been found in PCTs, and positive staining CD79a was present in 56.2% to 80% of cases studied (Schrenzel et al 1998, Ramos-Vara et al 1998, Ramos--Vara et al 2007). The CBL also can be stained by CD79a and immunoglobulin markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its nonspecific morphology, EMP is often misdiagnosed, therefore immunohistochemistry is necessary for definitive diagnosis (Morton et al 1986, Baer et al 1989, Ramos-Vara et al 2007). Tumour cells express CD79α, a transmembrane protein which is a part of B-cell antigen receptor (BCR).…”
Section: Introductionmentioning
confidence: 99%
“…Formalin-fixed, paraffin-embedded tissues were stained with hematoxylin-eosin and also prepared routinely for immunohistochemical analysis. The diagnosis of diffuse large B-cell lymphoma was based upon histomorphology and immunohistochemical detection of CD79a and/or CD20, as previously described (29). A second section was placed in RPMI 1640 and processed immediately for use in ex vivo bioassays.…”
mentioning
confidence: 99%